Founder personality and scaling decisions in entrepreneurial firms - Annette Becker; Hanna Hottenrott; Anwesha Mukherjee (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Personality drives human decision-making. Research on corporate research and development(R&D), however, typically considers strategic decision-making to be independent of the decisionmaker's personality traits. This study investigates the impact of CEO personality on scaling activities in young firms. In particular, we focus on R&D and investment decisions building on an entrepreneurial decision model that illustrates the different roles of major personality trait (ROCEAN: risk tolerance, openness to experience, conscientiousness, extraversion, neuroticism) in taking both R&D and investment decisions. Results based on detailed data from founders in 4,732 startups founded between 2011 and 2017 in Germany, show that scaling decisions in entrepreneurial firms are strongly imprinted by the CEO's personality. We find that higher risk tolerance and openness to experience result in a higher likelihood that the firm engages in R&D but only the former matters for levels of R&D expenditures. Comparing R&D decisions to tangible investments, we find that risk tolerance plays a more prominent role in the former but higher scores for openness also drive tangible investments. Founders with higher scores for agreeability and neuroticism are less likely to invest in growth in terms of R&D and tangible investments. More conscientious founders show lower R&D engagement but invest more in tangible assets. We discuss implications for entrepreneurship research and policy.
Keywords: D91; G11; L26; O32; O33; 330; Start-ups; Research & Development; Investment Decisions; Personality Traits; Risk tolerance